Poor and dissatisfied? Income poverty, poverty transitions and life satisfaction in Chile - Samman, Emma (2013)
Chile is an interesting country in which to study the relationship between poverty and subjective wellbeing, having experienced a remarkable fall in poverty over the past two decades. This paper explores how poverty status and transitions in and out of poverty contributed to life satisfaction in the late 2000s. Using new data for 2006 and 2009, we ind that poor people were more dissatisfied with life than the non-poor and that income gains did not appreciably affect the satisfaction of the poor while they remained below the poverty line. People who were not poor in either period exhibited higher satisfaction than those who were poor in both periods, while those who escaped poverty between 2006 and 2009 exhibited higher satisfaction than those who remained poor. In addition, people who fell into poverty in 2009 were no more or no less satisfied with their lives than those who were poor in both periods. The evidence suggests poor people may not have adapted to their circumstances, in contrast to much literature exploring income dynamics and life satisfaction, and also that people’s recent experiences appear to affect their perceptions more than more distant ones.